Pembuatan Sabun Padat Antiseptik Ekstrak Etanol Kulit Jeruk Lemon (Citrus Limon (L.) Burm. F.) - Eka Margaretha Sinaga; Nova Florentina Ambarwati; Barita Aritonang; Ahmad Hafizullah Ritonga (Jurnal Multidisiplin Madani, 2022)
Lemon peel waste (Citrus limon (L.) Burm.F.) contains secondary metabolites that function as antibacterials, such as alkaloids, flavonoids, and triterpenoids. This study aims to determine the formulation of antiseptic solid soap and the antibacterial activity of the ethanolic extract of the lemon peel by the diffusion method. The results showed the best formula for making antiseptic solid soap with ethanolic extract of lemon peel based on the requirements of SNI 06-4085-1996 was at a concentration of F3 (15%), homogeneous, had a pH of 8.54-9.82, foam height was around 3.5-4.7 cm, and a strong inhibition zone of about 12.48 mm. The conclusion of this study is that lemon peel has antibacterial properties that can kill the growth of Staphylococcus aureus bacteria.